The development of user interface (ui) for m-tix application in improving user experience (ux) using a/b testing method - Tasha Alyarisvi Nasution; Haikal Rahman (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
This study aims to develop the User Interface (UI) of the M-Tix application to improve the User Experience (UX) using the A/B Testing method. This study responds to user complaints regarding outdated design, confusing navigation, and technical issues such as sudden application closures. Using the ADDIE development model and involving 385 active users in Medan, this study conducted two main evaluations, namely A/B Testing and User Experience Questionnaire (UEQ). The results of A/B Testing showed a consistent and significant preference for the new design prototype (Design B) compared to the original application on all elements: Icons (64.9%), Layout (64.4%), Visuals (64.7%), Navigation (63.6%), and Coloring (64.3%). Furthermore, the UEQ analysis yielded an